2021
DOI: 10.1007/s00521-021-06370-3
|View full text |Cite
|
Sign up to set email alerts
|

Robust penalized extreme learning machine regression with applications in wind speed forecasting

Abstract: In extreme learning machine (ELM) framework, the hidden layer setting determines its generalization ability; and in presence of outliers in the training set, weights between hidden layer and output layer based on the least squares would be overly estimated. To address these two problems in ELM implementation, we extend robust penalized statistical framework in ELM and propose a general robust penalized ELM, which consists of two components (robust loss function and regularization item), for regression to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…We compare the proposed method with ELM [1], WELM [11], IRWELM [12], Welsch-ELM [22], Laplace-ELM [25], p-Welsch-ELM [28] on the artificial datasets and benchmark datasets. The root mean square error (RMSE) is chosen as the evaluation metric:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compare the proposed method with ELM [1], WELM [11], IRWELM [12], Welsch-ELM [22], Laplace-ELM [25], p-Welsch-ELM [28] on the artificial datasets and benchmark datasets. The root mean square error (RMSE) is chosen as the evaluation metric:…”
Section: Methodsmentioning
confidence: 99%
“…However, many practical applications cannot guarantee the error followed a normal distribution, which lead to a fact that ELM is highly susceptible to noise and outliers. Subsequently, the researchers proposed several loss function such as Huber [11], l 1 [12] and Pinball [13] and their corresponding ELM models. However, these loss functions were still less robust because they had a linear relationship with the training error and increased linearly with the training error.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to make more targeted recommendations and suggestions with guidance for the DMUs, an effective influence factor analysis method is needed for analysis. Common analysis methods include the least-square method [40], stochastic frontier method [41], Lasso method [42,43], robust penalized extreme learning machine regression [44], and physics-informed statistical learning method [45]. However, the efficiency value measured by the DEA method has a lower limit, and using traditional analysis methods is likely to cause serious bias.…”
Section: Influencing Factors Analysis Methodsmentioning
confidence: 99%
“…Yang et al (2022a) developed a highly accurate short-term load forecasting method using non-linear auto-regressive artificial neural networks with exogenous multi-variable input. Yang et al (2022b) presented a novel approach for shortterm electrical load forecasting by the radial basis function neural networks, and the result showed that the application of neural networks in short-term load forecasting is encouraging. Wang et al (2016) proposed an outstanding model based on a wavelet neural network to address the complex nonlinearities and uncertainties in forecasting the electric load, and the accuracy of the proposed model is better than the considered models.…”
Section: Introductionmentioning
confidence: 99%